The effect of iron versus iron plus zinc supplementation in children with malaria - Bugis Mardina Lubis; Danny Dasraf; Nelly Rosdiana; Bidasari Lubis; Munar Lubis; Syahril Pasaribu; Chairuddin P Lubis (Paediatrica Indonesiana, 2006)
Introduction Little is known about the potential interaction of ironand zinc given to increase hemoglobin and serum ferritin in chil-dren with malaria.Objective To study the effect of iron compared with a combination ofiron and zinc supplementation on children with falciparum malaria.Method Children with positive Plasmodium falciparum (n=86) wererandomly assigned to a daily supplementation of 6 mg iron/kg perday plus placebo or plus 10 mg zinc per day for 30 days. All childrenwere treated with the same regimen for the treatment of P. falciparum.Venous blood samples were collected at the start and end of thestudy. After 30 days of supplementation, the baseline and follow-upblood samples were analyzed.Results The increase of hemoglobin concentration in the ironplus placebo group was 0.58 g/dl, while in the iron plus zinc groupwas 0.09 g/dl (P<0.05). Serum ferritin concentration was high inboth groups before trial, yet there was no significant differenceafter iron supplementation.Conclusions Iron supplementation showed significant increasein hemoglobin concentration in children with positive P. falciparumtreated with the same regimen of treatment. Supplementation ofiron alone as well as iron plus zinc had been proven ineffective toiincrease serum ferritin in children with malaria.